Shariah Compliance for Islamic micro financing (Exploratory study in BAITUL MAAL WATTAMWIL in Depok City, Indonesia) - Rizki Ade Setiawan; Sepky Mardian (Fakultas Ekonomi, Universitas Bangka Belitung, 2021)
This study aims to analyze and evaluate the supervision of shariah compliance in the Baitul Maal Wattamwil (BMT) in the Depok City. The institutional and system approach is used to see the level of supervision carried out. This study uses primary data through interviews with the shariah supervisory board (SSB) and secondary data in the form of regulations issued by the Ministry of Cooperatives and Small and Medium Enterprises and similar research. This study found that the implementation of sharia supervision through an institutional approach or through a system approach still needed to be improved. In the institutional approach, there are still SSB that have not met the expected qualifications and the coaching process that has not yet run optimally, even though the composition, position, dual position and length of service of SSBs are in accordance with established rules and have been independent in carrying out sharia supervision. Whereas in the system approach carried out by the internal audit function, the external auditor and the Ministry of Cooperatives and Small and Medium Enterprises represented by the Dinas Koperasi have not been running optimally. Keywords: shariah compliance, shariah supervisory board, baitul maal wattamwil.